2001
DOI: 10.1097/00004424-200107000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Dynamics and Relation with Blood Flow

Abstract: The CSF segmentation algorithm is reproducible. Brain expansion was quickly regulated by a major extracerebral CSF flush flow, whereas ventricular CSF made only a very small contribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
94
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 207 publications
(97 citation statements)
references
References 34 publications
2
94
1
Order By: Relevance
“…SSS CSF flow has been characterized to have a peak Reynolds number, based on internal flow in a tube, ranging from 300 to 400 18 and Womersley number ranging from 5 to 17 32 . Phase-contrast MRI (PCMRI) measurements have quantified the total volumetric CSF pulsation, moving in and out of the intracranial space at the neck level, to be ~0.25 to 1 milliliter 3,37 . Peak systolic CSF flow velocities within the SSS range from ~1 to 10 cm/s in healthy subjects 7 .…”
Section: Introductionmentioning
confidence: 99%
“…SSS CSF flow has been characterized to have a peak Reynolds number, based on internal flow in a tube, ranging from 300 to 400 18 and Womersley number ranging from 5 to 17 32 . Phase-contrast MRI (PCMRI) measurements have quantified the total volumetric CSF pulsation, moving in and out of the intracranial space at the neck level, to be ~0.25 to 1 milliliter 3,37 . Peak systolic CSF flow velocities within the SSS range from ~1 to 10 cm/s in healthy subjects 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The pars posterior has the narrowest lumen of the cerebral aqueduct, while the ampulla has the widest lumen (19). Previous studies of CSF flow dynamics were made at a variety of different locations of the cerebral aqueduct, such as the mid-portion, the level of the inferior colliculi, or the junction with the fourth ventricle (18, 20, 21). To the best of our knowledge, however, there has been no study on the effects of scan level on CSF flow quantification.…”
mentioning
confidence: 99%
“…However, there have been many controversies regarding the true relationship between the cerebral blood flow (CBF) and CSF in mathematical models [8]. Previous models have varied from the simplest in which a portion of CBF produces CSF, to more complex models in which CSF production and CBF are mutually influenced and modulated [9]. Recent models have even suggested that the blood flow that produces CSF affects not only the quantity and pulsatility of CSF, but also the pulsatility that is transmitted from the cerebral blood vessels to the CSF [10].…”
Section: Hemodynamics and Csf Dynamicsmentioning
confidence: 99%
“…Recent models have even suggested that the blood flow that produces CSF affects not only the quantity and pulsatility of CSF, but also the pulsatility that is transmitted from the cerebral blood vessels to the CSF [10]. Various models have been postulated that describes the systemic arterial flow and whole cerebral blood flow, but as yet it is difficult to establish at the present time an accurate model that explains the relationship between cerebral blood flow and CSF pressure [9,11].…”
Section: Hemodynamics and Csf Dynamicsmentioning
confidence: 99%